Dose‐dependent efficacy of the glucose‐dependent insulinotropic polypeptide (GIP) receptor antagonist GIP(3‐30)NH2 on GIP actions in humans. Issue 1 (1st October 2020) - Gasbjerg, Lærke Smidt; Bari, Emilie J.; Stensen, Signe; Hoe, Bjørn; Lanng, Amalie R.; Mathiesen, David S.; Christensen, Mikkel B.; Hartmann, Bolette; Holst, Jens J.; Rosenkilde, Mette M.; Knop, Filip Krag
Abstract: The glucose‐dependent insulinotropic polypeptide (GIP) fragment GIP(3‐30)NH2 is a selective, competitive GIP receptor antagonist, and doses of 800 to 1200 pmol/kg/min inhibit GIP‐induced potentiation of glucose‐stimulated insulin secretion by >80% in humans. We evaluated the effects of GIP(3‐30)NH2 across a wider dose range in eight healthy men undergoing six separate and randomized 10‐mmol/L hyperglycaemic clamps (A–F) with concomitant intravenous infusion of GIP (1.5 pmol/kg/min; A–E) or saline (F). Clamps A to E involved double‐blinded, infusions of saline (A) and GIP(3‐30)NH2 at four rates: 2 (B), 20 (C), 200 (D) and 2000 pmol/kg/min (E), respectively. Mean plasma concentrations of glucose (A–F) and GIP (A–E) were similar. GIP‐induced potentiation of glucose‐stimulated insulin secretion was reduced by 44 ± 10% and 84 ± 10% during clamps D and E, respectively. Correspondingly, the amounts of glucose required to maintain the clamp during D and E were not different from F. GIP‐induced suppression of bone resorption and increase in heart rate were lowered by clamps D and E. In conclusion, GIP(3‐30)NH2 provides extensive, dose‐dependent inhibition of the GIP receptor in humans, with most pronounced effects of the doses 200 to 2000 pmol/kg/min within the tested range.